Analisis Tingkat Risiko Pada Bank Konvensional Milik Pemerintah Yang Terdaftar di Bei Periode 2015-2022 - Lilis Yulita; Citra Nurmani Putri; Dia Oktaviani; Ari Almansyah; Carmidah Carmidah (Jurnal Akuntan Publik, 2024)
The financial performance of government-owned conventional banks listed on the Indonesia Stock Exchange (BEI) has several levels of risk that can be used to assess. These risk levels include net interest margin (NIM), Loan to Deposit Ratio (LDR), Return On Assets (ROA), Non-Performing Loans (NPL), and Capital Adequacy Ratio (CAR). The aim of the research is to find out the level of risk faced by government-owned conventional banks in 2015-2022 using the risk levels of ROA, LDR, NPL, CAR and NIM. Quantitative descriptive research methodology was used in this research. By using financial reports for the 2015–2022 period, this research seeks to determine the degree of risk level of State-Owned Enterprise (BUMN) banks by using the NPL, ROA, NIM, CAR, LDR risk levels of state-owned banks. This research uses a case study methodology with secondary data collection. Time series and quantitative data analysis were included in this research. Purposive sampling is the method used in this research to determine the sample. The population and sample are all publicly traded banking companies which are State-Owned Enterprises registered on the IDX for the 2015-2022 period.